Clinical and ultrasonographic predictors of joint replacement for knee osteoarthritis: results from a large, 3-year, prospective EULAR study. Issue 4 (10th May 2009) - Conaghan, P G; D'Agostino, M A; Le Bars, M; Baron, G; Schmidely, N; Wakefield, R; Ravaud, P; Grassi, W; Martin-Mola, E; So, A; Backhaus, M; Malaise, M; et al.
Abstract : Objectives: To determine clinical and ultrasonographic predictors of joint replacement surgery across Europe in primary osteoarthritis (OA) of the knee. Methods: This was a 3-year prospective study of a painful OA knee cohort (from a EULAR-sponsored, multicentre study). All subjects had clinical evaluation, radiographs and ultrasonography (US) at study entry. The rate of knee replacement surgery over the 3-year follow-up period was determined using Kaplan–Meier survival data analyses. Predictive factors for joint replacement were identified by univariate log-rank test then multivariate analysis using a Cox proportional-hazards regression model. Potential baseline predictors included demographic, clinical, radiographic and US features. Results: Of the 600 original patients, 531 (88.5%), mean age 67±10 years, mean disease duration 6.1±6.9 years, had follow-up data and were analysed. During follow-up (median 3 years; range 0–4 years), knee replacement was done or required for 94 patients (estimated event rate of 17.7%). In the multivariate analysis, predictors of joint replacement were as follows: Kellgren and Lawrence radiographic grade (grade ≥III vs <III, hazards ratio (HR) = 4.08 (95% CI 2.34 to 7.12), p<0.0001); ultrasonographic knee effusion (≥4 mm vs <4 mm) (HR = 2.63 (95% CI 1.70 to 4.06), p<0.0001); knee pain intensity on a 0–100 mm visual analogue scale (≥60 vs <60) (HR = 1.81 (95% CI 1.15 to 2.83), p=0.01) and disease duration (≥5 years vs <5 years) (HR=1.63 (95% CI 1.08 to 2.47), p=0.02). Clinically detected effusion and US synovitis were not associated with joint replacement in the univariate analysis. Conclusion: Longitudinal evaluation of this OA cohort demonstrated significant progression to joint replacement. In addition to severity of radiographic damage and pain, US-detected effusion was a predictor of subsequent joint replacement.